2011
DOI: 10.1103/physreva.84.052111
|View full text |Cite
|
Sign up to set email alerts
|

Quantum measurements with preselection and postselection

Abstract: We study quantum measurement with preselection and postselection, and derive the precise expressions of the measurement results without any restriction on the coupling strength between the system and the measuring device. For a qubit system, we derive the maximum pointer shifts by choosing appropriate initial and finial states. A significant amplification effect is obtained when the interaction between the system and the measuring device is very weak, and typical ideal quantum measurement results are obtained … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 33 publications
6
112
0
Order By: Relevance
“…This generalizes the results of [59,60], and suggests that "classical" pointer states are not able to improve the SNR of postselected weak measurements.…”
supporting
confidence: 55%
“…This generalizes the results of [59,60], and suggests that "classical" pointer states are not able to improve the SNR of postselected weak measurements.…”
supporting
confidence: 55%
“…However, the amplification is saturated in an intermediate regime and rapidly drops in a strong measurement regime (s ≥ 1). This behavior results from a nonlinear aspect of the WVA [16][17][18][19]. Note that the maximum value of the frequency shift is larger as θ increases.…”
Section: B Evaluationmentioning
confidence: 96%
“…If the outcome of the measurement is exactly this weak value, it seems that we have an arbitrarily large outcome when the pre-and post-selections are nearly orthogonal [15]. However, when the weak value becomes large, non-linear effects of the von-Neumann measurement affect the outcome of the measurement [16][17][18][19]. As the result, the shift of the pointer variable has a maximum value and vanishes when the pre-and post-selected * Electronic address: anishi@yukawa.kyoto-u.ac.jp states are exactly orthogonal.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies [44,45] have shown that zero-mean Gaussian pointer state cannot improve the SNR when considering postselection probability. Needless to say Gaussian beam is classical and one may naturally ask how about using non-classical pointer states, and what kind of advantages they have?…”
Section: Introductionmentioning
confidence: 99%